Effect of Dietary Vitamin C Supplementation on the Growth Performance of KUB Chicken - Multazam, Syamsul; Haryanti, Ramdhani; Aini; Islami, Gita Nabilla (Jurnal Sain Peternakan Indonesia, 2025)
This study aims to determine the effect of vitamin C supplementation in rations on the performance of KUB chickens. The study was conducted from August 5 to October 10, 2025, in Pejanggik Village, Praya Tengah District, using a completely randomized design (CRD) with one direction, involving 100 DOC KUB chickens. The treatment consisted of four levels, namely P0 (control without vitamin C), P1, P2, and P3, each of which received additional vitamin C of 100, 200, and 300 mg/kg feed, with each treatment repeated 5 times and each replication containing five chickens. The data were analyzed using one-way analysis of variance (ANOVA) in SPSS version 26. The study showed that adding vitamin C to the feed had no significant effect on feed intake, body weight, or feed conversion efficiency.